2016
DOI: 10.1073/pnas.1423753113
|View full text |Cite
|
Sign up to set email alerts
|

Subunit stoichiometry and arrangement in a heteromeric glutamate-gated chloride channel

Abstract: The invertebrate glutamate-gated chloride-selective receptors (GluClRs) are ion channels serving as targets for ivermectin (IVM), a broad-spectrum anthelmintic drug used to treat human parasitic diseases like river blindness and lymphatic filariasis. The native GluClR is a heteropentamer consisting of α and β subunit types, with yet unknown subunit stoichiometry and arrangement. Based on the recent crystal structure of a homomeric GluClαR, we introduced mutations at the intersubunit interfaces where Glu (the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 76 publications
4
27
0
Order By: Relevance
“…We have recently shown that CHO cells transfected with the wild type GluClα subunit (αWT) alone display very weak responses to 10 mM Glu but robust responses to 500 nM IVM (Degani-Katzav et al, 2016). It was also shown that CHO cells transfected with the wild type GluClβ subunit (βWT) alone display very weak, rare responses to 10 mM Glu (Degani-Katzav et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that CHO cells transfected with the wild type GluClα subunit (αWT) alone display very weak responses to 10 mM Glu but robust responses to 500 nM IVM (Degani-Katzav et al, 2016). It was also shown that CHO cells transfected with the wild type GluClβ subunit (βWT) alone display very weak, rare responses to 10 mM Glu (Degani-Katzav et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that CHO cells transfected with the wild type GluClα subunit (αWT) alone display very weak responses to 10 mM Glu but robust responses to 500 nM IVM (Degani-Katzav et al, 2016). It was also shown that CHO cells transfected with the wild type GluClβ subunit (βWT) alone display very weak, rare responses to 10 mM Glu (Degani-Katzav et al, 2016). Others also reported irresponsiveness to Glu in human embryonic kidney (HEK) cells transfected with the wild type GluClβ subunit alone (Slimko et al, 2002; Frazier et al, 2013; Daeffler et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations